THE IMPLEMENTATION OF THE NEW SIRANSIJA APPLICATION ON ASN PRODUCTIVITY AT THE INVESTMENT, ESDM AND TRANSMIGRATION SERVICES OF GORONTALO PROVINCE - Ria Maku; Azis Rachman; Karlina Napu (LP2M Universitas Bina Mandiri Gorontalo, 2024)
Study this aim researching influence application New Siransija application to productivity Apparatus r State Civil on Service Investment , ESDM and Transmigration Province Gorontalo. it considered need done related with effort Upgrade service public by institution waiter public and Apparatus State Civil in environment Government Province Gorontalo, which since 2021 has apply New Sirisija application in whole ranks organization device area province. A total of 111 ASN people as population at a time as sample entirely is ASN employees on Service Investment, ESDM and Transmigration Province Gorontalo. Source of data used is the primary data obtained from deployment The next questionnaire processed with the help of the SPSS for Windows program. Results study concluded that there is significant influence Among Application New Sirisija application with ASN productivity at Service Investment, ESDM and Transmigration Province Gorontalo. Where number coefficient R Square 0.447 means that 44.7% of ASN productivity at Service Investment, ESDM and Transmigration could explained by application New Siransija application while the remaining 54.3%. influenced other factors.